Evolutionary patterns of Toll-like receptor signaling pathway genes in the Suidae. Issue 1 (December 2016) - Darfour-Oduro, Kwame; Megens, Hendrik-Jan; Roca, Alfred; Groenen, Martien; Schook, Lawrence
Abstract Background The Toll-like receptor (TLR) signaling pathway constitutes an essential component of the innate immune system. Highly conserved proteins, indicative of their critical roles in host survival, characterize this pathway. Selective constraints could vary depending on the gene's position within the pathway as TLR signaling is a sequential process and that genes downstream of the TLRs may be more selectively constrained to ensure efficient immune responses given the important role of downstream genes in the signaling process. Thus, we investigated whether gene position influenced protein evolution in the TLR signaling pathway of the Suidae. The members of the Suidae examined included the EuropeanSus scrofa (wild boar), AsianSus scrofa (wild boar), Sus verrucosus, Sus celebensis, Sus scebifrons, Sus barbatus, Babyrousa babyrussa, Potamochoerus larvatus, Potamochoerus porcus and Phacochoerus africanus . Results A total of 33 TLR signaling pathway genes in the Suidae were retrieved from resequencing data. The evolutionary parameter ω (dn/ds) had an overall mean of 0.1668 across genes, indicating high functional conservation within the TLR signaling pathway. A significant relationship was inferred for the network parameters gene position, number of protein-protein interactions, protein length and the evolutionary parameter dn (nonsynonymous substitutions) such that downstream genes had lower nonsynonymous substitution rates, more interactors and shorter protein length than upstream genes. Gene position was significantly correlated with the number of protein-protein interactions and protein length. Thus, the polarity in the selective constraint along the TLR signaling pathway was due to the number of molecules a protein interacted with and the protein's length. Conclusion Results indicate that the level of selective constraints on genes within the TLR signaling pathway of the Suidae is dependent on the gene's position and network parameters. In particular, downstream genes evolve more slowly as a result of being highly connected and having shorter protein lengths. These findings highlight the critical role of gene network parameters in gene evolution.